Enhanced recovery after cardiac surgery - Kołodziej, Tadeusz; Maciejewski, Tomasz; Mendrala, Konrad; Darocha, Tomasz; Węglarzy, Andrzej; Budziarz, Barbara; Kiermasz, Kazimierz; Kucewicz-Czech, Ewa (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2019)
The concept of early recovery after surgery (ERAS) consists of bundle interventions during the pre-, intra- and postoperative periods and team work. The ERAS, which is a multimodal strategy, enables one to limit the neurohumoral response to the surgery, maintain homeostasis, reduce the risk of complications, shorten the hospital stay, accelerate the return to everyday functioning, improve the patient’s satisfaction, achieve a satisfactory quality of life and finally reduce the treatment costs and eliminate any redundant and ineffective practices. Almost every patient can be classified for the ERAS strategy except for patients undergoing urgent and emergency surgery. The necessity to give up ERAS can result from poor organisation and management. Moreover, the procedure itself can be the cause of the lack of adherence to the planned standard. It is necessary to use protocols and checklists. While fulfilling this doctrine, the anaesthesiologist becomes a perioperative specialist.